Lesser known Sarcodes Useful in Female Disorders (Homoeopathy for All, 2021)
Sarcodes are homoeopathic drugs prepared from the healthy tissues or secretions of animals, including milk and hormones,but in absence of thorough human provings, the full potentials of these medicines could not be explored and some of them are not well-known to the homoeopathic professionals. But the utilities of some of these medicines have been documented from the clinical experiences of some of the leading homoeopathic practitioners. This article documents the symptomatology of a few such lesser known medicines like Folliculinum, Lac felinum, Lac vac defloratum, Oleum jecoris aselli, Oophorinum, Pituitarium anteriorium andSaccharum lactis infemale disorders.
Keywords: Lesser known sarcodes; Female disorders; Folliculinum; Lac felinum; Lac vac defloratum, Oleum jecorisaselli, Oophorinum